Effect of ventricular size and function on exercise performance and the electrocardiogram in repaired tetralogy of Fallot with pure pulmonary regurgitation - Shaji C Menon; Aditya K Kaza; Michael D Puchalski (Wolters Kluwer Medknow Publications, 2012)
Background: In repaired tetralogy of Fallot (TOF), exercise test parameters like peak oxygen uptake and ventilatory efficiency predict mortality. Studies have also suggested cardiac magnetic resonance (CMR)-derived right ventricular (RV) size threshold values for pulmonary valve replacement in repaired TOF. However, effects of proposed RV size on exercise capacity and morbidity are not known. Methods: The relationship between CMR-derived ventricular size, function, and pulmonary regurgitation (PR) and NYHA class, exercise performance, and electrocardiogram (ECG) was studied in patients of repaired TOF with pure PR in a retrospective review of records. Results: 46 patients (22 females), mean age 14 years (8−30.8), were studied. There was no relationship between CMR-derived ventricular size, function, or PR and exercise test parameters, or NYHA class. RV end systolic and end diastolic volume correlated positively with the degree of PR. QRS duration on ECG correlated positively with RV end-diastolic volume (P < 0.01, r2 = 0.34) and PR (P < 0.01, r2 = 0.52). Conclusions: In repaired TOF and pure PR, there is no correlation between ventricular size or function and exercise performance. RV size increases with increasing PR. Timing of pulmonary valve replacement in TOF with pure PR needs further prospective evaluation for its effect on morbidity and mortality.